2012
DOI: 10.1121/1.4742725
|View full text |Cite
|
Sign up to set email alerts
|

Cross-imaging system comparison of backscatter coefficient estimates from a tissue-mimicking material

Abstract: A key step toward implementing quantitative ultrasound techniques in a clinical setting is demonstrating that parameters such as the ultrasonic backscatter coefficient (BSC) can be accurately estimated independent of the clinical imaging system used. In previous studies, agreement in BSC estimates for well characterized phantoms was demonstrated across different laboratory systems. The goal of this study was to compare the BSC estimates of a tissue mimicking sample measured using four clinical scanners, each p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…It is common for most laboratories to create their own reference medium, making it difficult to reproduce measurements (e.g., Salles et al 2014;Wang and Shung 1997;Wear et al 2005). Calibrated commercial tissue-mimicking phantoms would alleviate this problem (Nam et al 2012). Other challenges, such as real-time display of parametric images, are still to be overcome; nevertheless, hardware improvements, such as graphic processing units, in addition to experimental validation as discussed here, allow us to be hopeful of a future clinical scanner with spectral characterization capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…It is common for most laboratories to create their own reference medium, making it difficult to reproduce measurements (e.g., Salles et al 2014;Wang and Shung 1997;Wear et al 2005). Calibrated commercial tissue-mimicking phantoms would alleviate this problem (Nam et al 2012). Other challenges, such as real-time display of parametric images, are still to be overcome; nevertheless, hardware improvements, such as graphic processing units, in addition to experimental validation as discussed here, allow us to be hopeful of a future clinical scanner with spectral characterization capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…As with attenuation estimation, controlled studies in phantoms and in animal models have demonstrated that backscatter parameters can be accurately measured and the results are independent of the imaging system used (Anderson et al, 2010; Nam et al, 2011, 2012a,b). Backscatter parameters have proven useful for monitoring changes in tissues and diagnosing disease (Feleppa et al, 1996; Garra et al, 1989; Insana et al, 1992, 1995).…”
Section: Cervical Tissue Mechanical Propertiesmentioning
confidence: 99%
“…Backscattered data was analyzed at depths between 10 and 50 mm, using data blocks of 14λ axially by 12 lines (roughly equivalent to 7.2 beamwidths) laterally. The bandwidth cutoff criterion for backscatter coefficient analysis was chosen as 7 dB higher than the noise floor, in accordance with previous studies [4], [13]. QUS parameters were estimated by performing an exhaustive ESD search in the range between 2 and 120 μm with a step size of 1 mm.…”
Section: Simulationsmentioning
confidence: 99%